Optimal control of an epidemic model with a saturated incidence rate - Laarabi, Hassan; Labriji, El Houssine Houssine; Rachik, Mostafa; Kaddar, Abdelilah (Nonlinear Analysis: Modelling and Control, 2012)
In this study we consider a mathematical model of an SIR epidemic model with a saturated incidence rate. We used the optimal vaccination strategies to minimize the susceptible and infected individuals and to maximize the number of recovered individuals. We work in the nonlinear optimal control framework. The existence result was discussed. A characterization of the optimal control via adjoint variables was established. We obtained an optimality system that we sought to solve numerically by a competitive Gauss–Seidel like implicit difference method.